2020
DOI: 10.1007/s00418-020-01858-w
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of nitric oxide and S-nitrosothiols in human skin

Abstract: Nitric oxide (NO) is related to a wide range of physiological processes such as vasodilation, macrophages cytotoxicity and wound healing. The human skin contains NO precursors (NO x). Those are mainly composed of nitrite (NO 2 −), nitrate (NO 3 −), and S-nitrosothiols (RSNOs) which forms a large NO store. These NO x stores in human skin can mobilize NO to blood stream upon ultraviolet (UV) light exposure. The main purpose of this study was to evaluate the most effective UV light wavelength to generate NO and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 71 publications
(103 reference statements)
2
21
0
Order By: Relevance
“…Although the roles of nNOS and eNOS have not yet been elucidated, they have been proposed to function in skin homeostasis, such as epidermal proliferation, keratinization, and the regulation of dermal blood flow. Previous studies demonstrated that iNOS synthesized a large amount of • NO during skin inflammation caused by ultraviolet exposure, psoriasis vulgaris, systemic lupus erythematosus, and wound healing [ 22 , 23 , 24 , 25 ]. iNOS activity was also shown to be significantly elevated in an LPS-induced inflammatory skin disease mouse model ( Figure 4 ) [ 19 ].…”
Section: Ros Generation In Skinmentioning
confidence: 99%
“…Although the roles of nNOS and eNOS have not yet been elucidated, they have been proposed to function in skin homeostasis, such as epidermal proliferation, keratinization, and the regulation of dermal blood flow. Previous studies demonstrated that iNOS synthesized a large amount of • NO during skin inflammation caused by ultraviolet exposure, psoriasis vulgaris, systemic lupus erythematosus, and wound healing [ 22 , 23 , 24 , 25 ]. iNOS activity was also shown to be significantly elevated in an LPS-induced inflammatory skin disease mouse model ( Figure 4 ) [ 19 ].…”
Section: Ros Generation In Skinmentioning
confidence: 99%
“…Upon stimulation by ultraviolet sunlight, the NO x stores in the skin can be redistributed to the blood stream where they may exert a positive physiological response by lowering vascular blood pressure (Weller 2016). Weller and colleagues have been studying the aspects of this beneficial sunlight-induced process for a number of years (Liu et al 2014;Mowbray et al 2009), and have now investigated the most effective range of ultraviolet wavelengths for generating NO (Pelegrino et al 2020). They used an NO meter with an electrochemical NO sensor to measure the release of free NO x species following irradiation with a range of ultraviolet wavelengths from both a controlled chemical aqueous solution simulacrum and human skin biopsy samples (Fig.…”
Section: "No Skin Off My Back" To Describe This Workmentioning
confidence: 99%
“…1,2,18 NO interaction with cellular targets can vary based on spatial and temporal distribution of NO influx within tumor cells and tumor microenvironment. 17,19 Thus, key factor linked to modulate the dichotomous effect of NO are the amount of NO released, the time-period and the spatial distribution of this signaling molecule in tumor tissue. 20 In addition, tumor microenvironment and heterogeneity also play an important role in the dichotomous effect of NO.…”
Section: Introduction: the Biological Importance Of Nitric Oxidementioning
confidence: 99%
“…3,17 Due to the NO instability, the use of NO donors has been successful used to exogenously delivery NO to a target site, in different biomedical applications. 19,26 The most common classes of NO donors, are sodium nitroprusside, organic nitrite and nitrate, furoxans, benzofuroxans, diazeniumdiolates (NONOates), S-nitrosothiols (RSNOs), Roussin's black salt (RBS) and metal nitrosyl complexes. 3,17,[27][28][29][30][31] The molecular representations of commonly used NO donors are shown in Figure 1.…”
Section: Introduction: the Biological Importance Of Nitric Oxidementioning
confidence: 99%
See 1 more Smart Citation